Mind the “Vaccine Fatigue” - Su, Zhaohui; Cheshmehzangi, Ali; McDonnell, Dean; da Veiga, Claudimar Pereira; Xiang, Yu-Tao (Frontiers in Immunology, 2022)
Background: Omicron scares and speculations are gaining momentum. Amid the nonstop debates and discussions about COVID-19 vaccines, the “vaccine fatigue” phenomenon may become more prevalent. However, to date, no research has systematically examined factors that shape people’s vaccine fatigue. To bridge the research gap, this study aims to investigate the antecedents that cause or catalyse people’s vaccine fatigue. Methods: A narrative literature review was conducted in PubMed, Scopus, and PsycINFO to identify factors that shape people’s vaccine fatigue. The search was completed on December 6, 2021, with a focus on scholarly literature published in English. Results: A total of 37 articles were reviewed and analysed. Vaccine fatigue was most frequently discussed in the context of infectious diseases in general at the pre-vaccination stage. Vaccine fatigue has been identified in the general public, the parents, and the doctors. Overall, a wide range of antecedents to vaccine fatigue has been identified, ranging from the frequency of immunization demands, vaccine side effects, misconceptions about the severity of the diseases and the need for vaccination, to lack of trust in the government and the media. Conclusion: Vaccine fatigue is people’s inertia or inaction towards vaccine information or instruction due to perceived burden and burnout. Our study found that while some contributors to vaccine fatigue are rooted in limitations of vaccine sciences and therefore can hardly be avoided, effective and empathetic vaccine communications hold great promises in eliminating preventable vaccine fatigue across sectors in society.